Principles of modern urology - Hemat, R. A. S. (Urotext, 2003)
Principles of Modern Urology is an authorative guide to urology and integrated urology. Principles of Modern Urology is an advanced urological textbook. This book begins by showing you how to implement your pathobiology, anatomy and physiology into practical simple approach to every client you meet. This book was written for medical student, resident and professional in medicine and especially urology. The author had adapted his proven teaching strategies into a unique approach that makes integrated urology accessible, and provides the foundations for understanding urology based upon the principles of structural pathobiology. Principles of Modern Urology presents well-integrated and practical approach to most urological condition. It is a versatile retrievable e-book. Principles of Modern Urology provides the reader with current concepts of the pathobiology and interventions for diseases. Anatomy, physiology, and radiology are also included within specific topical chapters. Principles of Modern Urology is based on the extensive international clinical and teaching experience of the author, both in traditional and integrated systems of medical schools.